2017
DOI: 10.1900/rds.2017.14.364
|View full text |Cite
|
Sign up to set email alerts
|

Association of Oxytocin with Glucose Intolerance and Inflammation Biomarkers in Metabolic Syndrome Patients with and without Prediabetes

Abstract: OXT may be a substantial surrogate predictive/prognostic tool and putative pharmacotherapeutic target in metabolic anomalies and related disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 25 publications
2
14
0
1
Order By: Relevance
“…Alisties was one of the most abundant genera of bacteria in mouse intestine and could ferment glucose and lactate to propionate, acetate, and succinate (Brown et al., ). These short chain fatty acids modulated the release of gut hormones controlling insulin release and appetite (Akour et al., ) In the previous study, the diet‐treated groups showed increased Lachnospiraceae_NK4A136_group (Shang et al., ) A metagenomic study found that some of the genes belonging to Akkermansia muciniphila were enriched in type 2 diabetic subjects (Qin et al., ). Here, we found that E. prolifera flavonoids significantly changed the gut microbiota composition with an increased proportion of Bacteroidetes and a decreased amount of the phylum Firmicutes .…”
Section: Discussionmentioning
confidence: 99%
“…Alisties was one of the most abundant genera of bacteria in mouse intestine and could ferment glucose and lactate to propionate, acetate, and succinate (Brown et al., ). These short chain fatty acids modulated the release of gut hormones controlling insulin release and appetite (Akour et al., ) In the previous study, the diet‐treated groups showed increased Lachnospiraceae_NK4A136_group (Shang et al., ) A metagenomic study found that some of the genes belonging to Akkermansia muciniphila were enriched in type 2 diabetic subjects (Qin et al., ). Here, we found that E. prolifera flavonoids significantly changed the gut microbiota composition with an increased proportion of Bacteroidetes and a decreased amount of the phylum Firmicutes .…”
Section: Discussionmentioning
confidence: 99%
“…In a large sample of men with metabolic syndrome, oxytocin concentrations were elevated compared with healthy controls, whereas the obese subjects of the present experiment displayed lower baseline oxytocin levels than their lean counterparts. Decreased oxytocin concentrations were reported in patients with metabolic syndrome or diabetes mellitus, suggesting a certain degree of oxytocin deficiency in diabetic patients . However, our preliminary finding of a positive relationship between HOMA‐IR and baseline oxytocin concentrations in the obese subjects argues against this assumption.…”
Section: Discussionmentioning
confidence: 68%
“…Decreased oxytocin concentrations were reported in patients with metabolic syndrome or diabetes mellitus, 10,11,15,16 suggesting a certain degree of oxytocin deficiency in diabetic patients. 1 However, our preliminary finding of a positive relationship between HOMA-IR and baseline oxytocin concentrations in the obese subjects argues against this assumption.…”
Section: Counter-regulatory Hormones Nefa Energy Expenditure and mentioning
confidence: 99%
“…For the second biomarker used in this study, PAI-1, reports in the literature indicate that the level of PAI-1 is associated with inflammation [ 44 ]. PAI-1 is also closely associated with endothelial dysfunction, as shown in different conditions [ 45 ], including in CV ischaemic disease and myocardial infarction [ 29 ].…”
Section: Discussionmentioning
confidence: 99%